Character evidence for the monophyly of the Microdesminae, with comments on relationships to Schindleria (Teleostei: Gobioidei: Gobiidae) - Gill, Anthony C.; Mooi, Randall D. (Zootaxa, 2010)
The composition of the Microdesminae has been inconsistently reported in recent molecular studies. A monophyletic Microdesminae consisting of both Indo-Pacific and New World/Atlantic genera is diagnosed here by the following synapomorphies: maxilla with elongate projection extending anteriorly over ascending processes of premaxilla; palatine medial process absent; single dorsal process on cleithrum; supracleithrum oriented vertically and closely applied to cleithrum; posttemporal with elongate posteroventral process; body slender and elongate, with associated increase in number of vertebrae and median fin rays (total vertebrae 42–66 with 19 or more precaudal vertebrae, total dorsal-fin rays 42–78, anal-fin rays 27–43), slender pelvis with anterior extensions of the pelvic intercleithral cartilage, and decrease in number of pelvic-fin rays (with a spine and 2–4 segmented rays); single dorsal fin; dorsal-fin spines usually 12 or more; predominantly 1:1 relationship between interneural spaces and anterior dorsal-fin pterygiophores; and first (supernumerary) ray on first anal pterygiophore a bilaterally paired, segmented ray. Several of these characters (particularly single dorsal process on cleithrum, posttemporal with elongate posteroventral process) support a possible relationship between microdesmines and Schindleria, as does dorsal gill-arch morphology.